2016
DOI: 10.21511/ppm.14(3).2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned obsolescence: consumer’s attitudes and perceptions of lifestyle brands in Durban, South Africa

Abstract: Planned obsolescence has become a strategy adopted by large corporations, for products to be produced with surprisingly short useful life spans. These shorter than expected product life spans ensure that consumers make regular repeat purchases of their favorite items. The monopoly of obsolescence of products is no longer the producers' prerogative and this by itself leads to unplanned obsolescence basically led by the consumers choice. This research study looks into consumer's attitudes and perceptions of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other authors consider the effects on the cultural industry of festivals [82,83], ethnic minorities [84], trademark registrations [85], innovative entrepreneurial ecosystem [86,87], venture creation [88], digitalization [89], communications [80], local and regional development [36] and creative cities [40,50], and social networks [90].…”
Section: Cultural Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors consider the effects on the cultural industry of festivals [82,83], ethnic minorities [84], trademark registrations [85], innovative entrepreneurial ecosystem [86,87], venture creation [88], digitalization [89], communications [80], local and regional development [36] and creative cities [40,50], and social networks [90].…”
Section: Cultural Industrymentioning
confidence: 99%
“…Other work has found that sectors that produce novel products are at the heart of the creative industry [200]. When coupled with policies that foster and sustain creativity, an innovative entrepreneurial ecosystem is created [86]. These studies examined industries related to the film industry [60,61], video games [65][66][67], social media [72,201], music [202], museums and art galleries [62][63][64], and fashion [59,203].…”
Section: Science Mapping 421 Authors' Keyword Co-occurrence Analysismentioning
confidence: 99%
“…Marketing influences customers' perceptions of products, product groups and companies. Thus, marketing can support, maintain and change customers' perception of brands or products, indirectly affecting the chances of achieving longer product longevity [21][22][23][24][25]. Meanwhile, product development activities include the available approaches for designers and engineers at a company.…”
Section: Theorymentioning
confidence: 99%
“…Much existing research on product longevity has focused on specific areas, to gain a deeper understanding of the mechanics that influence the longevity of consumer products. The findings show that business (Bakker et al 2014;Ertz et al 2019;Loon et al 2020;Konietzko et al 2020;Alqahtani & Gupta, 2017;Mohr et al 2001;Bradley & Guerrero, 2008), marketing, (Simpson & Radford, 2012;Sinclair et al 2018;Dixon et al 2010;Amolo & Beharry-Ramraj, 2016;Butz et al 1996), design, (Hagedorn et al 2018;Cupchik, 2017;den Hollander et al 2017;Bridgens et al, 2015), development, (Cooper, 2010;Rivera & Lallmahomed, 2016;Cooper 2004;Cooper, 1994;Bernard, 2019;Goel, 2006), legislation, (Bakker, 2017;European Commission, 2019), consumer behaviour, (Zhou & Gupta, 2019;Poppelaars et al 2018;Boot et al, 2008;Boks, 2018;Ackermann et al, 2018;Mugge et al 2006;van Nes & Cramer, 2005), purchase behaviour (Skene, 2018;Hou et al 2020;Nieuwenhuis, 2008;Montalvo et al, 2016;Cox et al, 2013;Dalhammer, 2015), and much more affect product longevity. For many SMEs, it might be difficult to identify how to approach, develop and succeed, as many factors influence each other.…”
Section: Introductionmentioning
confidence: 96%